1995
DOI: 10.1007/978-1-4899-1585-6_30
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Receptor Subtypes in Normal, Fetal, and Gravid Rabbit Bladder, Heart and Uterus

Abstract: In the rabbit bladder, pregnancy has been shown to induce a significant decrease in both muscarinic receptor density and response to muscarinic stimulation. Neonatal rabbit bladders have a high muscarinic receptor density and contractile response to bethanechol stimulation. The bladders from 7 gravid rabbits, 7 age-matched virgin controls, and 32 fetal rabbits of 3 week gestation were studied. Compared to control tissue, filtration binding demonstrated receptor density to be 24.3% lower in gravid bladder dome,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…These studies revealed a high muscarinic receptor density at birth; no significant changes in the cholinergic innervation over the first 6 weeks of postnatal development in the rabbit [17] but a decrease in potency and efficacy of carbachol and ATP during the first month of newborn rats [32]. So far, only one study has evaluated that muscarinic receptor subtypes are expressed to a significantly greater extent in fetal bladders [5]. In this study, we have studied muscarinic M 2 and M 3 receptor expression and function in juvenile and adult porcine detrusor to compare detrusor contractile function in premature and mature organisms.…”
Section: Discussionmentioning
confidence: 98%
“…These studies revealed a high muscarinic receptor density at birth; no significant changes in the cholinergic innervation over the first 6 weeks of postnatal development in the rabbit [17] but a decrease in potency and efficacy of carbachol and ATP during the first month of newborn rats [32]. So far, only one study has evaluated that muscarinic receptor subtypes are expressed to a significantly greater extent in fetal bladders [5]. In this study, we have studied muscarinic M 2 and M 3 receptor expression and function in juvenile and adult porcine detrusor to compare detrusor contractile function in premature and mature organisms.…”
Section: Discussionmentioning
confidence: 98%
“…The pressure in the bladder and the pressure generated by the gravid uterus during the last trimester may also affect the IAMNP and the fetal bladder. The pregnancy causes a decrease in muscarinic receptor density in both the rabbit bladder dome and the base by 24% to 41% [21], which explains previous observation of decreased contractile response to bethanechol [23]. It has been also reported that increased IAP causes cholinergic hyposensitivity in the adult rabbit bladders [6].…”
Section: Discussionmentioning
confidence: 64%
“…Muscarinic receptors of M3 subtype are also present, but with lower density. M1 and M4 are not found in the fetal and neonatal rabbit bladders [21].…”
Section: Discussionmentioning
confidence: 97%
“…In fetal rabbit bladder an increased density of both M 2 and M 3 (protein) has been reported, with no change in the M 2 /M 3 ratio. 20 Such increased receptor density might be involved in the increased response to the nonselective muscarinic agonist bethanechol in fetal rabbit bladder, 6 and might then also play a role in the increased response to muscarinic agonists in the present experiments. Using quantitative PCR we found that the expression levels of both M 2 and M 3 mRNA were highly increased in neonatal bladder (D0/D7) compared to adult, reaching highest significance at D7, and with a similar M 2 /M 3 ratio throughout ages (AE10, compared to AE9 at the protein level 21 ).…”
Section: Discussionmentioning
confidence: 93%